Karakteristik Tes Pilihan Majemuk dan Potensinya dalam Mengukur Kemampuan Berpikir Tingkat Tinggi - Mailool, Jefri (Jurnal Manajemen Pendidikan Kristen, 2023)
This study describes an effective strategy for building multiple-choice tests that can be implemented in assessing higher-order thinking. Its application in education is mainly to measure students' cognitive skills. Some of the steps used to construct this compound choice test include manipulating specific verb targets, reversing items, and using high-quality distractors. This study found that compound choice items have great potential for assessing higher-order thinking.